The Influence of Tiktok in Increasing Vocabulary for Elementary School in SMP 1 Muhammadiyah Banjarbaru - Intan Erwani; Muhammad Jalaluddin Romi; Muhammad Naziruddin Sawithy; Rohana Rohana; Saidah Ulfah; Izzah Supeni (ELITE Association Indonesia, 2022)
Tiktok is a digital application that provides various entertainment content in videos. This application has become popular in recent years because there are many exciting features and different public figures that also enliven and use this application. Afterward, no wonder the users can be found in various circles, from adults to children who often have access to Tiktok. Therefore, some people tend to get more information from this application. The writers conducted this research to determine whether this application affects the development of English vocabulary as a foreign language for young learners. Because the contents in Tiktok are not only available in one language but are also available in many languages, thus, this research is focused on young learners who already have access to the Tiktok application. Researchers used qualitative research instruments in the form of questionnaires and interviews to find the significance between vocabulary development and the use of the Tiktok application. The results obtained indicate a sufficient influence on the development of students' vocabulary.